2014
DOI: 10.1093/reseval/rvu024
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of policies for formal knowledge transfer from European universities and public research institutes to firms

Abstract: We use survey data for 247 European universities and 40 public research organizations to investigate the effects of institutional policies on four outcomes of transfer performance (R&D agreements with companies, patent applications, licence agreements, and start-ups established). We find that the effects of policies to establish clear rules, improve transparency, and provide financial or non-financial incentives vary by outcome. Improving transparency by publishing the policies for licencing or intellectual pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 42 publications
(60 reference statements)
1
15
0
2
Order By: Relevance
“…Our observations and awareness of challenges that many SMEs face with, e.g., a limited number of employees, knowledge, and skills, have confirmed the limited use of BM methods (e.g., Canvas) and tools (e.g., spreadsheets like Excel) for BMI [101]. As already exposed by Florén and Agostini [102], many enterprises have difficulties in finding proper approaches, methods, and tools for systematic business model innovation.…”
Section: Practical Implicationssupporting
confidence: 62%
“…Our observations and awareness of challenges that many SMEs face with, e.g., a limited number of employees, knowledge, and skills, have confirmed the limited use of BM methods (e.g., Canvas) and tools (e.g., spreadsheets like Excel) for BMI [101]. As already exposed by Florén and Agostini [102], many enterprises have difficulties in finding proper approaches, methods, and tools for systematic business model innovation.…”
Section: Practical Implicationssupporting
confidence: 62%
“…Moreover, to our knowledge, research by Barjak et al (2014) alone specifically addresses SMEs. Therefore, a generic BMI model taking into account the antecedents of BMI as well as outcomes is developed and tested.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Once established, many KTOs are able to make independent decisions in the area of IP management and knowledge transfer. This ability, combined with its age and experience, number and qualifications of its staff, degree of autonomy from the institution, organizational structure and degree of centralization of services can influence knowledge transfer performance (for reasons of brevity we omit references to the relevant literature, a review can be found in a sister paper to this article, see Barjak et al 2015).…”
Section: Characteristics Of the Kto And The Institutionmentioning
confidence: 99%
“…Several institutional characteristics and policies can influence performance as well; previous work points to ownership (public-private), size, the existence of science departments or a medical faculty, research excellence and business orientation, institutional by-laws and policies for instance with regard to IP protection and management, licensing and the distribution of commercialization revenues (for supporting evidence see again Barjak et al 2015).…”
Section: Characteristics Of the Kto And The Institutionmentioning
confidence: 99%